Advances in the prevention and treatment of congenital cytomegalovirus infection. Issue 1 (February 2016) - James, Scott H.; Kimberlin, David W.
Abstract : Purpose of review: Cytomegalovirus (CMV) is the most common cause of congenital infection in the world. Symptomatic infants are at increased risk of developing permanent sequelae, including sensorineural hearing loss and neurodevelopmental delay. Advances in the treatment and prevention of congenital CMV infection are a high priority nationally and globally. Recent findings: In symptomatic infants, antiviral therapy with 6 months of oral valganciclovir improves hearing and neurodevelopmental outcomes. Strategies to prevent congenital or maternal CMV infections, including the use of CMV hyperimmune globulin and development of a maternal vaccine, have yet to yield positive results. Summary: The clinical significance of congenital CMV infection, developments in antiviral therapy, and efforts to prevent congenital disease are herein reviewed.